2021
DOI: 10.1038/s41467-020-20614-1
|View full text |Cite
|
Sign up to set email alerts
|

H2AK121ub in Arabidopsis associates with a less accessible chromatin state at transcriptional regulation hotspots

Abstract: Although it is well established that the Polycomb Group (PcG) complexes maintain gene repression through the incorporation of H2AK121ub and H3K27me3, little is known about the effect of these modifications on chromatin accessibility, which is fundamental to understand PcG function. Here, by integrating chromatin accessibility, histone marks and expression analyses in different Arabidopsis PcG mutants, we show that PcG function regulates chromatin accessibility. We find that H2AK121ub is associated with a less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 69 publications
2
42
0
1
Order By: Relevance
“…We found that the protein expression level of LC3 was increased. This finding is consistent with previous studies (François et al, 2015;Alvarez-Arellano et al, 2018). LC3 is a universal biochemical index for observing autophagy and assessing autophagic activity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We found that the protein expression level of LC3 was increased. This finding is consistent with previous studies (François et al, 2015;Alvarez-Arellano et al, 2018). LC3 is a universal biochemical index for observing autophagy and assessing autophagic activity.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, NLRP3, caspase-1, and IL-1β were increased in the brain tissues of the AD model mice, which was consistent with previous research results (François et al, 2014). In in vitro experiments, NLRP3, caspase-1, and IL-1β were increased in BV2 cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The canonical hierarchical model proposed that PRC2-mediated H3K27me3 does not intrinsically impact the chromatin structure but serves as a docking site for PRC1 complex [63]. PRC1 in turn catalyzes the mono-ubiquitination of histone H2A (H2Aub), thus preventing the recruitment of nucleosome remodeling factors and subsequent gene silencing (Figure 1C) [63][64][65][66][67]. In line with this notion, genome-wide chromatin binding profiles demonstrated co-occupancy of PRC1 and PRC2 at many H3K27me3 deposition loci from animals to plants [9,[67][68][69][70][71][72][73].…”
Section: Prc1-mediated H3k27me3 Reading and Gene Silencingmentioning
confidence: 99%